Verbalizers leave marks: Evidence from Greek - Vassilios Spyropoulos; Anthi Revithiadou; Phoevos Panagiotidis (Morphology, 2015)
In this article we provide evidence that the verbalizing v head in Greek has a morphological exponence in many more verbs than is apparent. Although, at first sight, verbs in the traditional second conjugation inflectional class (which exhibit non-root stress, e.g., aɣap-ó ‘I love’, poθ-ó ‘I desire’) do not seem to contain an overt piece of verbalizing morphology, we show that they take a vocalic extension consisting of an abstract vocalic slot. This slot, which can either be filled in with vocalic material or remain empty, undertakes the function of a verbalizer. Two major gains of this analysis is that it provides solid evidence for a v head as a verbalizer and not as a composite Voice-verbalizing head and that it proposes a unified treatment of the Greek verb morphology without extensively retreating to stem allomorphy.